2020
DOI: 10.1002/cche.10374
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and cooking quality improvement of brown rice noodles prepared with extruded rice bran

Abstract: Background and objectives Wholegrain foods have gained great attention due to their benefits on health. However, the texture, taste, and cooking quality of wholegrain foods are not good because of the bran in wholegrain. The objectives of this study were to improve the quality of brown rice noodles with rice bran that was treated by extrusion cooking. In this study, brown rice noodles with extruded rice bran (BRN‐ERB) were prepared to improve their quality compared to white rice noodles (WRN) and brown rice no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Extruded flours with 50% teff resulted in significantly higher TDF values than those of containing 25% teff flour. Many studies have shown significant effects of extrusion on fibre composition in many matrices [ 61 , 62 ], resulting in a reduction in the ratio of insoluble to soluble fibre; but few works have reported increases in total fibre content overall [ 63 , 64 ], as it occurred in this work. High shear–temperature combination of different mechanism by which extrusion could cause carbohydrate–lipid–protein complexes, lead to the formation of resistant starch [ 65 ].…”
Section: Resultsmentioning
confidence: 61%
“…Extruded flours with 50% teff resulted in significantly higher TDF values than those of containing 25% teff flour. Many studies have shown significant effects of extrusion on fibre composition in many matrices [ 61 , 62 ], resulting in a reduction in the ratio of insoluble to soluble fibre; but few works have reported increases in total fibre content overall [ 63 , 64 ], as it occurred in this work. High shear–temperature combination of different mechanism by which extrusion could cause carbohydrate–lipid–protein complexes, lead to the formation of resistant starch [ 65 ].…”
Section: Resultsmentioning
confidence: 61%
“…However, according to our previous study, steam treatment at temperatures of 100 • C improved starch swelling as well as the performance of the gel during extrusion (Yang et al, 2023). These results are contrary to the effects observed with steam treatment above 120 • C. Steam at a temperature of 100 • C can effectively break down the molecular chains of the starch molecules and thus increase starch swelling (Ma et al, 2021). These findings and reasoning suggest that treatment with non-SS at 100 • C has the potential to improve the rehydration performance of rice noodles.…”
Section: Introductionmentioning
confidence: 68%
“…Antioxidant capacities in rice cake had a similar change trend with the contents of phenolics, and were related to their contents of phenolic. Antioxidant capacities of WRC were the lowest, which was due to the fact that phenolics were mainly existed in bran layer, while rice bran was less in WRC (Wu et al., 2020). The levels of phenolic and flavonoid in GBR were boosted during germination, consequently, the antioxidant activities of GBR cake were enhanced (Munarko et al., 2021).…”
Section: Resultsmentioning
confidence: 99%